2019
DOI: 10.2147/ndt.s221901
|View full text |Cite
|
Sign up to set email alerts
|

<p>Is Autism Inborn And Lifelong For Everyone?</p>

Abstract: Autism or autism spectrum disorder (ASD) is described as a lifelong condition with core behavioural symptoms appearing during infancy or early childhood. Genetic and other effects occurring during the earliest times of life are thought to play a significant contributory role to the presentation of autism, denoting that autism is typically seen as an innate or inborn condition. Such descriptions have, and continue to, define autism research and clinical practice. Inspection of the existing research literature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Anderson et al 2014 ; Cederlund et al 2008 ; Fein et al 2013 ; Gillberg et al 2016 ; Helles et al 2017 ; Helt et al 2008 ; Orinstein et al 2015a , b ). In each of these studies, the proportion of individuals reported to have lost all their autistic symptoms is small (generally less than 10%; Whiteley et al 2019 ) and subsequent, more detailed data analyses have often indicated some persisting subtle difficulties in the domains of social-communication, cognition, and emotional recognition. There may also be certain mental health difficulties, particularly related to phobias and ADHD (Orinstein et al 2015a , b ).…”
Section: Is There Recovery From Autism?mentioning
confidence: 99%
“…Anderson et al 2014 ; Cederlund et al 2008 ; Fein et al 2013 ; Gillberg et al 2016 ; Helles et al 2017 ; Helt et al 2008 ; Orinstein et al 2015a , b ). In each of these studies, the proportion of individuals reported to have lost all their autistic symptoms is small (generally less than 10%; Whiteley et al 2019 ) and subsequent, more detailed data analyses have often indicated some persisting subtle difficulties in the domains of social-communication, cognition, and emotional recognition. There may also be certain mental health difficulties, particularly related to phobias and ADHD (Orinstein et al 2015a , b ).…”
Section: Is There Recovery From Autism?mentioning
confidence: 99%
“…Lastly, we targeted only adults with ASD. Basically, the three main traits of ASD are found at birth and last a lifetime [ 54 ]. From this viewpoint, the pathogenesis of ASD lasts from birth to adulthood, but several factors, such as comorbidities, lifestyle, and drugs, could affect gene expression.…”
Section: Limitationsmentioning
confidence: 99%
“…ASD is for most people a lifelong disability. 2 Whilst developmental trajectories vary across individuals as a result of maturation and interventions 3,4 there is a substantial degree of persistence of core ASD features over a lifetime for many. This means that individualised support provisions are required across the lifespan for most individuals with ASD.…”
Section: Introductionmentioning
confidence: 99%